2015
DOI: 10.1007/s00221-015-4312-y
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hemispheric desynchronization of the human MT+ during visually induced motion sickness

Abstract: Visually induced motion sickness (VIMS) is triggered in susceptible individuals by stationary viewing of moving visual scenes. VIMS is often preceded by an illusion of self-motion (vection) and/or by inappropriate optokinetic nystagmus (OKN) responses associated with increased activity in the human motion-sensitive middle temporal area (MT+). Neuroimaging studies have reported predominant right hemispheric activation in MT+ during both vection and OKN, suggesting that VIMS may result from desynchronization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…A study of functional connectivity in response to visual motion (but not nausea) demonstrated that compared to a resting state, visual motion stimulation reduced functional connectivity between MT+/V5, which was activated by this task, and several visual processing areas, including cuneus and lingual gyrus [12]. More recently, Miyazaki et al reported inter-hemispheric desynchronization between left and right MT+ during a brief (6-minute) visual stimulation that induced mild motion sickness [13]. This study compared connectivity during a global motion stimulus with that during a control, local motion stimulus, and also noted a trend towards decreased inter-hemispheric correlation in the primary visual cortices (V1) (though not statistically significant).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of functional connectivity in response to visual motion (but not nausea) demonstrated that compared to a resting state, visual motion stimulation reduced functional connectivity between MT+/V5, which was activated by this task, and several visual processing areas, including cuneus and lingual gyrus [12]. More recently, Miyazaki et al reported inter-hemispheric desynchronization between left and right MT+ during a brief (6-minute) visual stimulation that induced mild motion sickness [13]. This study compared connectivity during a global motion stimulus with that during a control, local motion stimulus, and also noted a trend towards decreased inter-hemispheric correlation in the primary visual cortices (V1) (though not statistically significant).…”
Section: Discussionmentioning
confidence: 99%
“…Functional connectivity response to visual motion stimulation (but not nausea) shows reduced functional connectivity between MT+/V5 and several other striate and extrastriate visual processing areas [12] in comparison to a resting state. Recently, Miyazaki et al [13] found that a brief (6 minutes) visual stimulation that was accompanied by mild motion sickness resulted in desynchronization between left and right MT+ areas for the high frequency (>0.1 Hz) component of the BOLD fMRI signal. Few other studies exist that have evaluated functional brain connectivity response to motion sickness-induced nausea following sustained stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous study (Miyazaki et al, 2015), the participants were classified into two groups: the VIMS group (n = 8, all men, including 2 authors; mean age ± SD, 32.3 ± 7.2 years) who experienced VIMS in the experimental session; and the healthy group (n = 6, 2 women and 4 men including 2 authors; mean age ± SD, 33.3 ± 7.2 years) who did not get VIMS. Details on this grouping criterion are provided in Miyazaki et al (2015). Two in the VIMS group could not recover during the experimental session and were thus excluded from this analysis aimed at investigating the recovery phase from VIMS.…”
Section: Participantsmentioning
confidence: 99%
“…VIMS generally emerges and evolves slowly during exposure to a motion stimulus, and, when the stimulus is removed, the individual slowly recovers from the MS symptoms over time. As for the emergency and evolutional phase of VIMS, several neuroimaging studies have revealed the underlying brain response (Napadow et al, 2013;Miyazaki et al, 2015;Farmer et al, 2015;Toschi et al, 2017). Napadow et al (2013) measured the functional magnetic resonance imaging (fMRI) activity of female participants during the presentation of translating black/white stripes for a long enough period to induce VIMS, finding that nausea was associated with a broad network of brain areas including the insula, cingulate cortex, and limbic regions, which are known to process stress, emotion, and interoception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation